Interaction of Rifampin and Darunavir-Ritonavir or Darunavir-Cobicistat In Vitro - Roberts, Owain (Antimicrob Agents Chemother, 2017)
Treatment of HIV-infected patients coinfected with Mycobacterium tuberculosis is challenging due to drug-drug interactions (DDIs) between antiretrovirals (ARVs) and antituberculosis (anti-TB) drugs. The aim of this study was to quantify the effect of cobicistat (COBI) or ritonavir (RTV) in modulating DDIs between darunavir (DRV) and rifampin (RIF) in a human hepatocyte-based in vitro model. Human primary hepatocyte cultures were incubated with RIF alone or in combination with either COBI or RTV for 3 days, followed by coincubation with DRV for 1 h. The resultant DRV concentrations were quantified by high-performance liquid chromatography with UV detection, and the apparent intrinsic clearance (CL(int.app.)) of DRV was calculated. Both RTV and COBI lowered the RIF-induced increases in CL(int.app.) in a concentration-dependent manner. Linear regression analysis showed that log(10) RTV and log(10) COBI concentrations were associated with the percent inhibition of RIF-induced elevations in DRV CL(int.app.), where β was equal to −234 (95% confidence interval [CI] = −275 to −193; P < 0.0001) and −73 (95% CI = −89 to −57; P < 0.0001), respectively. RTV was more effective in lowering 10 μM RIF-induced elevations in DRV CL(int.app.) (half-maximal [50%] inhibitory concentration [IC(50)] = 0.025 μM) than COBI (IC(50) = 0.223 μM). Incubation of either RTV or COBI in combination with RIF was sufficient to overcome RIF-induced elevations in DRV CL(int.app.), with RTV being more potent than COBI. These data provide the first in vitro experimental insight into DDIs between RIF and COBI-boosted or RTV-boosted DRV and will be useful to inform physiologically based pharmacokinetic (PBPK) models to aid in optimizing dosing regimens for the treatment of patients coinfected with HIV and M. tuberculosis.